Utilization of Quizizz as an Online Learning Media for Early Childhood - Karim, Nur Adha (Raudhatul Athfal: Jurnal Pendidikan Islam Anak Usia Dini, 2024)
This research aims to see the benefits of Quizizz as an online learning media for young children. The approach used is quantitative with a quasi-experimental design. The research sample consists of 142 early childhood children aged 5-6 years at the Al-Amin Batuangkar Kindergarten. The research lasted for three months, from January to March 2024. Data collection techniques include observation, structured interviews with teachers, and questionnaires to measure students' perceptions of using Quizizz. The collected data is analyzed using descriptive and inferential statistics to test the research hypothesis. The research results show that the use of Quizizz significantly increases interest in learning and understanding number material in Arabic in young children. Children who used Quizizz show higher increases in learning outcomes compared to the control group who used conventional learning methods. Based on these findings, it is recommended that educators and educational institutions consider integrating Quizizz or similar platforms in the learning curriculum for early childhood, considering its positive impact on children's motivation and learning outcomes. This research makes an important contribution to the field of early childhood education, especially in the use of educational technology to improve the quality of learning.